Large‐Amplitude Mountain Waves in the Mesosphere Accompanying Weak Cross‐Mountain Flow During DEEPWAVE Research Flight RF22. Issue 18 (17th September 2018) - Fritts, David C.; Vosper, Simon B.; Williams, Bifford P.; Bossert, Katrina; Plane, John M. C.; Taylor, Michael J.; Pautet, P.‐Dominique; Eckermann, Stephen D.; Kruse, Christopher G.; Smith, Ronald B.; Dörnbrack, Andreas; Rapp, Markus; et al.
Abstract: Mountain wave (MW) propagation and dynamics extending into the upper mesosphere accompanying weak forcing are examined using in situ and remote‐sensing measurements aboard the National Science Foundation/National Center for Atmospheric Research Gulfstream V (GV) research aircraft and the German Aerospace Center Falcon. The measurements were obtained during Falcon flights FF9 and FF10 and GV Research Flight RF22 of the Deep Propagating Gravity Wave Experiment (DEEPWAVE) performed over Mount Cook, New Zealand, on 12 and 13 July 2014. In situ measurements revealed both trapped lee waves having zonal wavelengths of λ x  ~ 12 km and less, and larger‐scale, vertically propagating MWs primarily at λ x  ~ 20–60 km and ~100–300 km extending from west to ~400 km east of Mount Cook. GV Rayleigh lidar measurements from 25‐ to 60‐km altitudes showed that the weak forcing and zonal winds that increased from ~12 m/s at 12 km to ~40 and 130 m/s at 30 and 55 km, respectively, enabled largely linear MW propagation and strong amplitude growth with altitude into the mesosphere. GV Na lidar and airglow imager measurements revealed an extensive MW response from ~70 to 87 km with large amplitudes and vertical displacements at λ x  ~ 40–300 km but with both decreasing with altitude approaching a critical level near 90 km. These MWs exhibited large‐scale MW breaking and among the largest sustained momentum fluxes observed in the mesosphere. UK Met Office Unified Model simulations of the RF22 MW event captured many aspects of the observed MW field and revealed that despite the dominant large‐scale MW responses in the stratosphere, the major momentum fluxes accompanied smaller‐scale waves. Key Points: Weak orographic forcing and conducive propagation conditions at lower altitudes can yield large mountain wave amplitudes in the mesosphere Mesospheric mountain waves can extend over 1, 000 km around the source terrain and persist for many hours after forcing ceases Mesospheric mountain waves having {lambda} h  < 100 km can achieve very large momentum fluxes and exhibit strong overturning and instabilities